Design of a 660 V / 15 kVA single-phase UPS based on series connection of low-output-voltage modular UPS - Lazzarin, Telles B.; Barbi, Ivo (Eletrônica de Potência, 2012)
Critical loads are usually provided by sources of uninterruptible power supply (UPS). Such devices have output voltages equivalent to levels found in commercial power grids. However, when high output voltages are required there is still no standard solution to achieve the desired level of voltage. This paper proposes the development of a high-output-voltage single-phase UPS based on the series connection of several low-output-voltage modular UPSs. The main idea is to obtain a commercial UPS in one standard module which can connect several modules in series until reaching the required output voltage. This solution allows high-voltage to be obtained employing only available modules and being of low cost it is suitable for industrial application. In this context, this paper introduces some principles regarding the series connection of UPS, which translates into the serial connection of voltage source inverters (VSIs). Furthermore, the study provides the experimental verification of the proposed system through the development of a prototype of 660V and 15kVA, obtained from the connection of three single-phase modules of 220V and 5kVA.